Izobraževanje za lokalno trajnostno oskrbo s hrano - Resnik Planinc, Tatjana (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
This paper looks at local sustainable food supplies from the aspect of education and youth awareness. Through analysis of the present circumstances, the authors offer suggestions of how to implement the chosen theme into a geography lesson within primary and secondary schools. They are convinced the implementation of a chosen theme into a compulsory educational programme proves its importance in everyday life, in the development of an individual and for society as a whole, thereby offering us an assurance that the main ideas will reach the majority of the population.
Keywords: education; geografija; geography; hrana; izobraževanje; lokalne skupnosti; oskrbovalne verige; pouk; Slovenia; Slovenija; trajnostna strategija; učni programi